Analysis of the Readiness of Malang City Government in Implementing Accrual- Based Government Accounting Standard - Kariyoto Dr (Jurnal VOK@SINDO, 2016)
This study aims to determine the readiness of the government of Malang in implementing accrual-based government accounting standards. Data were collected through observation and indepth interviews with managers and employees of the financial section on education which includes the village chief and the village secretary in Malang. The data collected was then analyzed using qualitative method by using an interpretive approach. The results show that the readiness of the government of Malang in the implementation of accrual-based Government Accounting Standards (SAP) is a reflection of a formality. This is supported by the government regulations that require all local governments, including the government of Malang, to implement accrual-based Government Accounting Standards. The complexity of the financial statements is the main factor that make the financial managers of 31 SKPD in Malang city government deny to implementat of accrual-based Government Accounting Standards. In addition, the other findings show that: 1) the understanding of accrual-based Government Accounting Standards in Kedungkandang district. (agricultural- based district) is still low; 2) the implementation of accrualbased Government Accounting Standards in Klojen district (trading-based district) is still low; 3) the understanding of accrual-based Government Accounting Standards in Klojen district. (industrial-based district) is good enough; 4) the understanding of accrual-based Government Accounting Standards in Sukun district. (industrial-based district) is fairly good; 5) the understanding of accrual-based Government Accounting Standards in Lowokwaru district. (teacher-based district) is highly good. Regarding this, in terms of organizational culture, Malang city government is obliged to apply accrual-based government accounting standards. Malang City government should conduct training for different bases of districts as well as regularly Kedungkandang agricultural base training intensity must be more than the other districts.